Comparative study of Serum Creatinine and Serum Glucose Level between Term and Preterm Neonates in a Tertiary Care Hospital - Sayed, Md Abu; Begum, Fardoushi; Islam, Syeda Nafisa; Hossain Khan, Md Ismail; Uddin, Md Belal (TAJ: Journal of Teachers Association, 2022)
Introduction: A large number of babies are being delivered in our country prematurely. Renal function and glucose metabolism are not fully developed in these babies Resulting in disturbance of their homeostasis. Objectives: This study was conducted to measure serum creatinine and serum glucose in term and preterm infants and compare their values to find out any significant difference. Methodology: This cross-sectional study included a total of hundred cases of neonates (term babies 50, preterm babies 50) who were admitted to the Paediatric inpatient department or delivered in the obstetrics department of Rajshahi Medical College Hospital during the period of July 2012 to December 2012. Data were collected from the parents who gave written informed consent. To test the Results, whether they were statistically significant or not, ‘z' test was applied. Result: Among the total 100 neonates in the term group, the male-female ratio was 1:1.5, and in the preterm group, it was 1:1. In the preterm groups, 20 (20%) babies had a gestational age between 35-37 weeks, 15 (15%) babies had a gestational age between 32-34 weeks, and the rest 15 (15%) babies were in between 28-31 weeks. Here, man serum creatinine value in term babies was 0.89 ±0.16 mg/dl, whereas that in the preterm babies was 1.02±0.36. In the term babies, serum creatinine value > 0.9 mg/dl was in 36%, and in the preterm babies, it was in 48%. Values of serum creatinine were found higher in the preterm neonates, which was statistically significant (Z = 2.338, P < 0.05). This study also showed mean serum glucose level in the term babies 4.14±2 mmol/l and in the preterm 3.46 ±1.92. Hypoglycemia was found in 14% of term babies and 46% of preterm babies. Statistical analysis showed no significant difference between the means of the two groups (z test value 1.735 and p-value >0.05). Conclusion: Raised serum creatinine is common in preterm babies. But, hypoglycemia may occur in both groups without any significant difference. TAJ 2021; 34: No-2: 64-70